Impact of Sub-MIC Eugenol on Klebsiella pneumoniae Biofilm Formation via Upregulation of rcsB - Elken, Emad Mohammed; Tan, Zi-ning; Wang, Qian; Jiang, Xiu-yun; Wang, Yu; Wang, Yi-ming; Ma, Hong-xia (Frontiers in Veterinary Science, 2022)
The Rcs phosphorelay system is present in many members of the Enterobacteriaceae. The aim of this study was to illustrate the possible mechanisms of eugenol on ultimate targets of Klebsiella pneumoniae (K. pneumoniae) Rcs phosphorelay, rcsB, and impact on biofilm formation. The minimum inhibitory concentration (MIC) of eugenol against K. pneumoniae KP1 and KP1 ΔrcsB strain was determined using the 2-fold micro-dilution method. Biofilm was measured by crystal violet staining. Transcriptome sequencing was performed to investigate sub-MIC eugenol on K. pneumoniae, and gene expression at mRNA level was analyzed by RT-qPCR. In vitro biofilm formation test and molecular docking were used to evaluate the effect of eugenol and to predict potential interactions with RcsB. MicroScale Thermophoresis (MST) was conducted for further validation. MIC of eugenol against K. pneumoniae KP1 and KP1 ΔrcsB strain was both 200 μg/ml. Transcriptome sequencing and RT-qPCR results indicated that rpmg, degP, rnpA, and dapD were downregulated, while rcsB, rcsD, rcsA, yiaG, and yiaD were upregulated in the eugenol-treated group. ΔrcsB exhibited a weakened biofilm formation capacity. Additional isopropyl-β-d-thiogalactoside (IPTG) hinders biofilm formation, while sub-MIC eugenol could promote biofilm formation greatly. Docking analysis revealed that eugenol forms more hydrophobic bonds than hydrogen bonds. MST assay also showed a weak binding affinity between eugenol and RcsB. These results provide significant evidence that rcsB plays a key role in K. pneumoniae biofilm formation. Sub-MIC eugenol facilitates biofilm formation to a large extent instead of inhibiting it. Our findings reveal the potential risk of natural anti-biofilm ingredients at sub-MIC to treat drug-resistance bacteria.